Linking Corporate Social Responsibility with Reputation and Brand of the Firm - Jintao Lu; Licheng Ren; Yifan He; Wenfang Lin; Justas Streimikis (Amfiteatru Economic)
There are no agreements among scientists in terms of relationships between Corporate Social Responsibility (CSR), Corporate Identity and Corporate Image (CI), Corporate Reputation (CR), and Corporate Brand (CB), and their mutual impacts as well the definition of these constructs cause a lot of scientific debates among scholars. The paper analyses the relationship between CSR, Corporate Image, Corporate Reputation and Corporate Brand and their outcomes linked to the financial and other benefits of the firm and society. The main studies that are dealing with this subject were analysed, and the theoretical model that is linking these constructs was developed. The proposed model can be used for carrying empirical studies in specific industries and branches of the economy in order to assess the main measures to increase Corporate Reputation and maximise its outcomes